PENGARUH MOTIVASI INVESTASI DAN PENGETAHUAN INVESTASI TERHADAP MINAT INVESTASI DI PASAR MODAL PADA MAHASISWA FEB UNISMA DIMASA PANDEMI - Ilham Muhammad Aurum Mulyono; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study is to determine the effect of investment motivation and investment knowledge on the investment interest of students of the Faculty of Economics and Business, Islamic University of Malang in the capital market. The population in this study were accounting students of the Faculty of Economics and Business, Islamic University of Malang, class of 2018 - 2020. The sample used was accounting students of Faculty of Economics and Business, Islamic University of Malang, Class of 2018 - 2020 who had taken the Capital Market Money Market course. The sampling technique in this study was purposive sampling technique and the number of samples selected was 92 respondents. data collection in this study using the questionnaire method. The data analysis method in this study used multiple linear regression analysis using the SPSS 16 application. The tested data used were concurrent hypothesis testing (f), determinant coefficient (r2) and partial test (t). based on the results of research and test results that have been carried out, it shows that simultaneously the investment motivation variabel and investment knowledge have a significant effect on the investment interest variabel.Keywords: investment motivation, investment knowledge, investment interest, capital market money market